Dual endothelin‐1 receptor antagonism attenuates platelet‐mediated derangements of blood coagulation in Eisenmenger syndrome. (22nd June 2018) - Kevane, B.; Allen, S.; Walsh, K.; Egan, K.; Maguire, P. B.; Galligan, M. C.; Kenny, D.; Savage, R.; Doran, E.; Lennon, Á.; Neary, E.; Ní Áinle, F.
Abstract : Essentials Eisenmenger syndrome is characterised by thrombotic and hemorrhagic risks of unclear aetiology. Calibrated automated thrombography was used to assess these coagulation derangements. Platelet activity supported abnormalities in procoagulant and anticoagulant pathway function. Endothelin‐1 antagonism appeared to ameliorate these derangements. Summary: Aims: The mechanisms underlying the competing thrombotic and hemorrhagic risks in Eisenmenger syndrome are poorly understood. We aimed to characterize derangements of blood coagulation and to assess the effect of dual endothelin‐1 receptor antagonism in modulating hemostasis in this rare disorder. Methods: In a 10‐month recruitment period at a tertiary cardiology referral center, during which time there were over 14 000 outpatient consultations, consecutive subjects with Eisenmenger syndrome being considered for macitentan therapy ( n = 9) and healthy volunteers ( n = 9) were recruited. Plasma thrombin generation in platelet‐rich and platelet‐poor plasma was assessed by calibrated automated thrombography prior to and following therapy. Results: Median peak plasma thrombin generation was higher in platelet‐rich plasma obtained from Eisenmenger syndrome subjects relative to controls (median peak thrombin [25th–75th percentile]: 228.3 [206.5–258.6] nm vs. 169.9 [164.3–215.8] nm ), suggesting a critical mechanistic role for platelets in supporting abnormal hypercoagulability in Eisenmenger syndrome. Abnormal enhanced sensitivity to the anticoagulant activity of activated protein C was also observed in platelet‐rich plasma in Eisenmenger syndrome, suggesting that derangements of platelet activity may influence the activity of anticoagulant pathways in a manner that might promote bleeding in this disease state. Following 6 months of macitentan therapy, attenuations in the derangements in both procoagulant and anticoagulant pathways were observed. Conclusions: Abnormal platelet activity contributes to derangements in procoagulant and anticoagulant pathways in Eisenmenger syndrome. Therapies targeting the underlying vascular pathology appear to ameliorate these derangements and may represent a novel strategy for the management of the competing prothrombotic and hemorrhagic tendencies in this disorder.